Origami‐Inspired Modular Electro‐Ribbon Actuator for Multi‐Degrees of Freedom Motion - Ningzhe Hou; Jian Wen; Yuhan Pan; Majid Taghavi (Advanced Intelligent Systems, 2024)
Origami robots, inspired by an ancient form of paper folding art, are capable of achieving high displacement in a lightweight and compact design that conventional robots can hardly attain. It, however, remains a challenge to drive origami robots with in situ active materials that imply minimal added mass and complexity and can be easily controlled to achieve multiple actuation modalities. Herein, inspired by the Twisted Tower origami structure, dielectrophoretic liquid zipping actuation concept is employed to develop a modular architecture, capable of achieving complicated motions with multiple degrees of freedom (DoF). The experimental results show a maximum of 3.9 degrees tilting per layer toward any desired direction, a 56.1% contraction of the original length, and 5.4 degrees twisting per layer. Each layer can generate a maximum contractile force of 1.03 N with a maximum 64.7% power efficiency and 2.775 W kg−1 power‐to‐weight ratio. A modified heterochiral arrangement of this modular actuator is proposed to enhance controllability across various movement modes. Its use in robotic‐wrist‐like actuation has been demonstrated, highlighting its significant potential for integration into soft robotic multi‐DoF structures, such as continuum arms.